Review on yew tree (Taxus spp.) - D Yazdani; S Shahnazi; Sh Rezazadeh; M Pirali Hamadani (Institue of Medicinal Plants, ACECR, 2005)
Importance of yew tree (Taxus spp.) originates from the entering of Taxol (Paclitaxel) in the treatment of breast cancer since 1982. Taxus spp. is one of the Taxaceae family, distributed in North America, Europe, meditranean region, Asia and North forests of Iran. Efficacy of Taxol in the treament of some cancers and low concentration of this compound in tree, stimulated semi synthetic preparation of taxol from other more aboundant compounds such as baccation-III which is found with higher concentrations in all tree tissues. Despite entering some other routs for preparation of taxol e.g. cell culture, cultivation and studies on yew tree is in high importance, therefore review on this plant was made by authors.